Corporate governance and Islamic social reporting disclosure: evidence from Islamic bank in ASEAN - Anggita Renata Sari; Misnen Ardiansyah; Narong Hassanee (Universitas Islam Negeri Walisongo Semarang, 2025)
Purpose - This study aims to analyze the effect of CEO power, independent board of commissioners, capital structure, and firm size on Islamic social reporting disclosure, as well as to explore the role of profitability as a moderating variable. Method - Using the random effect model and data analysis with EViews 12, the research sample includes Islamic banks in Malaysia, Indonesia, and Brunei Darussalam during the period from 2018 to 2023, with a population of 20. Result - CEO power has no significant effect on isr disclosure, while the independent board of commissioners and firm size have a significant positive effect. Capital structure shows a positive but insignificant effect, with profitability moderating the relationship between capital structure and firm size on isr disclosure. Implication - Good corporate governance and management commitment are essential for enhancing ISR disclosure, which is key to maintaining the reputation and transparency of Islamic banks in ASEAN. Originality - This study is the first to examine Islamic social reporting disclosure by integrating corporate governance factors and profitability across three ASEAN countries.